The Issue on Dualistic Role of Neutrophils in Carcinogenesis and Their Possible Use for Treatment of Malignant Neoplasms - Gabashvili, Anna N.; Vasiukova, Anastasiia A.; Rakitina, Aleksandra S.; Garanina, Anastasiia S. (Biochemistry (Moscow), 2025)
Neutrophils are phagocytic leukocytes of the myeloid series, which are the most common myeloid cells in human blood, normally accounting from 65 to 80% of all circulating leukocytes. Over the years of investigation of these cells, more and more evidence has emerged indicating functional plasticity of neutrophils and their ambiguous role in the tumor development. Similarly to the M1/M2 classification of macrophages, the N1/N2 paradigm could be applied to neutrophils, where N1-neutrophils exhibit tumor-suppressive properties, and N2-neutrophils contribute to tumor development and immune suppression. An important natural feature of neutrophils is their mobility and ability to overcome physical barriers, thus these cells, as well as their vesicles and membranes, could be used to deliver therapeutic drugs to tumor cells. In addition, neutrophils themselves could be activated and mobilized to fight the tumor. This review describes current state of research on the role of neutrophils in carcinogenesis, as well as possible approaches of using these cells and their derivatives as systems for targeted delivery of therapeutic drugs for treatment of malignant neoplasms.